The Correlation Between Vocabulary Mastery and Students' Achievement in Writing Narrative Texts of The Ninth-Grade of SMP Swasta PGRI 1 Medan - Hema Ribka Novelouisa Lumbanraja; Nurmahyuni Asrul; Dwi Suci maniarsih (Teaching English and Language Learning English Journal, 2025)
This study was conducted to determine whether there was a relationship between vocabulary mastery and writing achievement of ninth grade students at SMP Swasta PGRI 1 Medan, particularly in writing narrative texts with theme “Slice of Life”. The research employed a quantitative approach with a correlational design. The sample consisted of 16 ninth grade students, who represented the only ninth grade class in SMP Swasta PGRI 1 Medan, therefore, the sampling technique used was total sampling. The instruments of this study included 20 multiple choice items of vocabulary test and narrative writing test assessed based on five aspects. The findings of this study showed that the majority of ninth grade students were at medium level in both vocabulary mastery (62.5%) and writing achievement (50%). The Pearson correlation test indicated that ther was a positive, moderate relationship between vocabulary mastery and writing achievement (r = 0.496), however the relationship was not statistically significant (sig. = 0.051 > 0.005). Thus, this study concluded that there was no significant correlation between students’ vocabulary mastery and their achievement in writing narrative text. These results that students’ writing achievement may be influenced by several other factor besides vocabulary mastery.